Archaeology and Memorial Processes of the Anti-Francoist Guerrilla in the Casaio Mountains (Carballeda de Valdeorras, Ourense) - Tejerizo-García, Carlos; Rodríguez Gutiérrez, Alejandro; Álvarez Cobian, Olalla (Madrygal. Revista de Estudios Gallegos, 2020)
The mountains of Casaio, in the northeastern part of the current province of Ourense, became, during the 40s and 50s of the past century, one of the fundamental centers for the articulation of the de anti-Francoist guerrilla. Since the year 2016 we are carrying out an archaeological and historical project on the known as the “Ciudad de la Selva”, a group of camp sites occupied by the guerrilla and one of the main nodes of the Federación de Guerrillas de León-Galicia. Concurrently, we have developed an anthropological project with the aim of analysing the process of construction of the memory within local communities in relation with violence, repression and resistance of the guerrilla movement. In this paper we present the first results and reflections on this latter project. We present several examples of memorial processes whose connection is the relationship between memory and materiality. Moreover, from this perspective, we will confront the concept of memory developed both academically and socially since the enactment of the known as “Historic Memory Law”.
Keywords: Memory; Materiality; Anti-Francoist Guerrilla; Oral Interviews; Northwestern Iberia